Dynamics of Coupled Structures, Volume 1 Proceedings of the 32nd IMAC, A Conference and Exposition on Structural Dynamics, 2014 - Allen, Matt; Mayes, Randy; Rixen, Daniel (Conference Proceedings of the Society for Experimental Mechanics Series, 2014)
This critical collection examines a range of the dynamics of coupled structures, from reduced order models to industrial applications of substructuring to experimental studies of joints and joined structures, as presented in early findings and case studies from the Proceedings of the 32nd IMAC, A Conference and Exposition on Structural Dynamics, 2014. The collection includes papers in the following general technical research areas: ·         Substructuring and the Ampair Wind Turbine Test Bed ·         Experimental Dynamic Substructuring ·         Reduced Order Models ·         Experimental Studies of Joints and Joined Structures ·         Analytical/Numerical Modeling of Joints ·         Industrial Applications of Substructuring.